Il trattamento con farmaci intravitreali anti-VEGF in pazienti naïve in Italia. (August 2018) - Albrecht, M; Nica, M; Colombo, D; Ferri, C; Tadini, P; Introini, U; Bandello, F
Background: Ranibizumab and aflibercept are approved in Italy for the anti-VEGF (vascular-endothelial-growth-factor) treatment of four retinal diseases: neovascular age-related macular degeneration (AMD), diabetic macular edema (DME), myopic choroidal neovascularization (mCNV), and retinal vein occlusion (RVO). The objective was to gather information about their utilization in a real-world setting of an Italian hospital. Methods: A retrospective study was conducted at San Raffaele Hospital on 2, 117 naïve patients who started treatment in 2013-2015. Results: The mean age of patients was 70 years. The larger groups of patients were those affected by AMD (60.5%) and DME (23.4%). Almost 40% of DME patients were treated in both eyes. On average, AMD patients received 3.97 injections/patient/year; DME: 4.22; mCNV: 2.01; RVO: 3.15. Among treated eyes, 75% received no more than 4 injections/year. One eye out of five was treated only once a year. A trend was highlighted in AMD and DME: the frequency of administrations per eye/year increased along the years considered. In AMD and DME patients who were treated in both eyes, the first eye received (on the average) at least 50% more of the drug than the second eye did. Of the total intravitreal drug expenditure for the whole cohort, more than a half was due to AMD. The overall mean annual expenditure per treated patient was €2, 684 (mCNV €1, 319 – DME €3, 101), for 3.8 administrations/year on average. Conclusion: The present work aims at providing useful, real-life information about the therapeutic patterns and costs for intravitreal anti-VEGF treatment of retinal diseases in Italy.